Peran Dinas Pemberdayaan Perempuan Perlindungan Anak Pengendalian Penduduk dan Keluarga Berencana (DP3AP2KB) Kota Malang dalam Penanganan Kekerasan dalam Rumah Tangga (KDRT) - Dia Melita (ABDI KARYA : Pengabdian Kepada Masyarakat, 2026)
Malang City faces a serious problem related to the high rate of domestic violence (KDRT), which is a major concern for the Malang City Government through the DP3AP2KB in protecting and handling victims. This study uses a descriptive qualitative method to identify factors influencing the increase in domestic violence cases. Data were collected through field observations as primary data and literature and archives as secondary data. The analysis results indicate that economic factors, especially poverty, are the main drivers of domestic violence because they trigger conflict in the household. In addition, low public understanding and awareness of domestic violence and women's rights exacerbate the situation, where the lack of information makes victims unaware of their rights and access to assistance. This study aims to provide more effective policy recommendations in the prevention and handling of domestic violence, thereby strengthening protection for victims and creating a safer environment in Malang City.